Choosing a place to live in maintaining family resilience: The perspective of maqashid al-usrah - Arifandi, Saddam; Rouf, Abd. (LP3M Universitas Islam Zainul Hasan Genggong, 2025)
: The obligation of a husband to provide a residence for his wife is one of the key aspects of Islamic marriage. However, many couples still live with their parents or in-laws due to economic limitations, potentially affecting family dynamics. This study aims to analyze the most appropriate place to live after marriage in maintaining family resilience from the perspective of maqashid al-usrah according to Jamaluddin 'Athiyyah. Using a normative legal approach and qualitative analysis of literature, this study applies seven indicators of maqashid al-usrah to evaluate different residential patterns. The findings show that living independently in one's own home is more conducive to achieving family harmony, especially in terms of maintaining marital intimacy, minimizing parental interference, and strengthening the husband's leadership role. Among the seven indicators, tahqiq al-sakn wa al-mawaddah wa al-rahmah and tandhim al-janib al-mu’assasi li al-’usrah are the most influential. In conclusion, while living with parents or in-laws is not inherently negative, residing in an independent home is more aligned with the objectives of Islamic family resilience.